Improving Drought Stress Tolerance in Ramie (Boehmeria nivea L.) Using Molecular Techniques - Rasheed, Adnan; Jie, Yucheng; Nawaz, Muhammad; Jie, Hongdong; Ma, Yushen; Shah, Adnan Noor; Hassan, Muhammad Umair; Gillani, Syed Faheem Anjum; Batool, Maria; Aslam, Muhammad Talha; Naseem, Ahmad Raza; Qari, Sameer H. (Frontiers in Plant Science, 2022)
Ramie is one of the most significant fiber crops and contributes to good quality fiber. Drought stress is one of the most devastating abiotic factors which is accountable for a substantial loss in crop growth and production and disturbing sustainable crop production. Drought tolerance (DT) impairs growth, plant water relation, and nutrient uptake. Ramie has evolved a series of defense responses to cope with DS. There are numerous genes regulating the DT mechanism in ramie. The morphological and physiological mechanism of DT is well-studied; however, modified methods would be more effective. The use of novel genome editing tools like clustered regularly interspaced short palindromic repeats (CRISPR) is being used to edit the recessive genes in crops to modify their function. The transgenic approaches are used to develop several drought-tolerant varieties in ramie, and further identification of tolerant genes is needed for an effective breeding plan. Quantitative trait loci (QTL) mapping, transcription factors (TFs) and speed breeding are highly studied techniques, and these would lead to the development of drought-resilient ramie cultivars. The use of hormones in enhancing crop growth and development under water scarcity circumstances is critical; however, using different concentrations and testing genotypes in changing environments would be helpful to sort the tolerant genotypes. Since plants use various ways to counter DS, investigating mechanisms of DT tolerance in plants will lead to improved DT in ramie. This critical review summarized the recent advancements on DT in ramie using novel molecular techniques. This information would help ramie breeders to conduct research studies and develop drought tolerant ramie cultivars.